Handbook for effective supervision of instruction - Neagley, Ross L.; Evans, N. Dean (Englewood Cliffs, New Jersey : Prentice-Hall, 1964)
Many books have been written in recent years on the theory of modern school supervision. The tasks of definition and identification of the supervisory role have been reasonably well accomplished. However, in the thinking of many supervisors and administrators, few guidelines have been developed to help reconcile the theory of supervision with the practical teaching-learning situations which school officials and teachers meet each day.
1. The Theory and function of supervision in the modern public school system -- 2. Organization and function of supervision in the small district -- 3. Organization and function of supervision in the intermediate-size district -- 4. Organization and function of supervision in larger districts -- 5. The Superintendent, assistant superintendent, and curriculum coordinator at work in supervision -- 6. The Principal at work in supervision -- 7. Specialist, department heads, team leaders, and helping teachers -- 8. Factors that influence change -- 9. Working with individuals to improve instruction -- 10. Working with groups to improve instruction -- 11. How to organize and carry out a program of curriculum study and development -- 12. The Evaluation of supervision programs -- 13. A look ahead.
Includes bibliographical references and index.
Keywords: SCHOOL SUPERVISION